2013
DOI: 10.1371/journal.pone.0073218
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of Litopenaeus vannamei in Response to White Spot Syndrome Virus Infection

Abstract: Pacific white shrimp (Litopenaeus vannamei) is the most extensively farmed crustacean species in the world. White spot syndrome virus (WSSV) is one of the major pathogens in the cultured shrimp. However, the molecular mechanisms of the host-virus interaction remain largely unknown. In this study, the impact of WSSV infection on host gene expression in the hepatopancreas of L. vannamei was investigated through the use of 454 pyrosequencing-based RNA-Seq of cDNA libraries developed from WSSV-challenged shrimp or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(67 citation statements)
references
References 47 publications
3
63
0
1
Order By: Relevance
“…Annotated unigenes showed matches with unigenes of Daphnia pulex (12 %), Tribolium castaneum (6 %), Pediculus humanus (5 %), Branchiostoma floridae (3 %), Crassostrea gigas (3 %), Ixodes scapularis (3 %), Nasonia vitripennis (3 %), Capitella teleta (3 %), followed by Litopenaeus vannamei (3 %). Our results agree with those of Guo et al (2013) and Xiaohan Chen et al (2013b), indicating that mostly all or the majority of unigenes are similar to those of Daphnia pulex, Tribolium castaneum, and Pediculus humanus; this might be attributed to the close phylogenetic relationship to these species, for which a great deal of genetic information is available over all of the annoted genes presented. On the other hand, the remaining annotated unigenes show certain similarity with other species, a fact which might be attributed to the relatively limited amount of the L. vannamei protein sequences available in the database.…”
Section: Functional Annotationsupporting
confidence: 90%
See 1 more Smart Citation
“…Annotated unigenes showed matches with unigenes of Daphnia pulex (12 %), Tribolium castaneum (6 %), Pediculus humanus (5 %), Branchiostoma floridae (3 %), Crassostrea gigas (3 %), Ixodes scapularis (3 %), Nasonia vitripennis (3 %), Capitella teleta (3 %), followed by Litopenaeus vannamei (3 %). Our results agree with those of Guo et al (2013) and Xiaohan Chen et al (2013b), indicating that mostly all or the majority of unigenes are similar to those of Daphnia pulex, Tribolium castaneum, and Pediculus humanus; this might be attributed to the close phylogenetic relationship to these species, for which a great deal of genetic information is available over all of the annoted genes presented. On the other hand, the remaining annotated unigenes show certain similarity with other species, a fact which might be attributed to the relatively limited amount of the L. vannamei protein sequences available in the database.…”
Section: Functional Annotationsupporting
confidence: 90%
“…An average 87 % of differentially expressed transcripts were annotated with the different databases; nevertheless, 13 % had low sequence homology with the sequences that were already known through public databases. These data matched with the aforementioned data presented by Zeng et al (2013) and by Chen et al (2013b). In the same way, they obtained 80 % similarity with currently reported transcripts.…”
Section: Identification Of Differently Expressed Transcriptssupporting
confidence: 89%
“…The Toll-Dorsal signaling pathway is necessary in the resistance of a host to virus infection (31)(32)(33)(34)(35). Toll receptors can trigger the Toll-Dorsal signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, RNA-seq analysis of mucosal immune responses revealed signatures of intestinal barrier disruption and pathogen entry following Edwardsiella ictaluri infection in channel catfish [11]. 454 pyrosequencing-based RNA-Seq results revealed that apoptosis, mitogen-activated protein kinase signaling, toll-like receptor signaling, Wnt signaling and antigen processing and presentation pathways functioned importantly in defending against White Spot Syndrome Virus in white shrimp [10]. Similar studies were conducted in Vibrio harveyi challenged Asian seabass [8] and Japanese sea bass [17], white shrimp with Taura syndrome virus [20], and Chinese shrimp challenged with White Spot Syndrome Virus [21].…”
Section: Disease Resistance and Immunologymentioning
confidence: 99%
“…It has also been proven to be a sufficient tool to capture the genes and pathways involved in many biological processes of aquatic animals [7][8][9]. Therefore, the use of RNA-seq has attracted the attention of aquaculture researchers in many areas of research, and successful example studies have been reported in many economical aquaculture species [10][11][12][13].…”
mentioning
confidence: 99%